Local knowledge of the Baduy Community of South Banten (Indonesia) on the traditional landscapes - JOHAN ISKANDAR; BUDIAWATI S. ISKANDAR (Biodiversitas Journal of Biological Diversity, 2017)
Iskandar J, Iskandar BS. 2017. Local knowledge of the Baduy Community of South Banten (Indonesia) on the traditional landscapes. Biodiversitas 18: 928-938. The Baduy people are a distinctive group of 11,620 people representing 3,395 households who live in an area of 5.136,58 hectares in the mountainous region of South Banten, Java. Traditional Baduy land cultivated by Baduy alone is described as tanah Baduy (Baduy land). This paper discusses the local knowledge of the Baduy community on the traditional landscapes. A qualitative method was used in this study. The result of the study shows that based on the Baduy categories, the Baduy landscape can be divided into four types, mainly forest, swiddens, gardens, and settlements. These landscape types have been traditionally managed based on the Traditional Ecological Knowledge (TEK) and beliefs. As a result, the Baduy people have continuously been able to practice traditional swidden cultivation, despite population growth and the depletion of the forest around them.